Brain Tumor : Molecular Biology, Pathophysiology, and Clinical Symptoms - Vanessa Essianda; Annisa Diyanabila Indrasari; Puji Widyastuti; Talitha Syahla; Rohadi Rohadi (Jurnal Biologi Tropis, 2023)
Brain tumors are one of the most malignant tumors that occur in humans. It accounts for approximately 1.35% of all malignant neoplasms and 29.5% of cancer deaths. This article was written with the aim of knowing more about molecular biology, phatophysiology, and clinical symptoms of brain tumor. The method used is a literature review combined with a search for related sources from National Center for Biotechnology Information (NCBI), Google Scholar, and Research Gate. The results of this literature review of the articles carried out can be concluded that brain tumors often cause symptoms of physiological disorders, such as focal signs, fatigue and headaches or behavioral disorders including hallucinations, depression, anxiety, decreased attention and awareness. Brain tumors can also arise spontaneously without a family history or previous genetic inheritance pattern. In conclusion, cytogenetic and molecular abnormalities in brain tumors can be seen in numerical and structural chromosomal changes, gene amplification and overexpression, deletions and small-scale mutations and epigenetic deregulation.